IDENTIFICATION OF SUITABLE LOCATIONS OF OCEAN ENERGY IN LABUAN STATE - GIS APPROACHED - JAMALUDDIN, MUHAMMAD REDZUAN (Universiti Teknologi PETRONAS, 2020)
Ocean energy indicates the energy carried by ocean waves as one of the main sources of renewable energy. Renewable energy is very crucial in this globalization because non-renewable energy has become very limited. Because of the limitation of non-renewable energy, ocean energy needs to be identified to deal with this challenge. Labuan is an island located on the coast of the state of Sabah which is surrounded by the oceans which may have some potential ocean energy. However, the location of ocean energy must be identified to be produced. Therefore, this research had been done an analysis at Labuan that can harvest ocean energy to overcome this energy crisis. However, due to the limitation of data availability, the identification of these ideal locations in Labuan was difficult to determine. In dealing with ocean data, the data analysis method in physical oceanography has normally been used.